The Perspective on Bio-Nano Interface Technology for Covid-19 - Kamaraj, Sathish-Kumar (Frontiers in Nanotechnology, 2020)
The field of bio-nano interfaces paves the way for a better understanding, development and implementation of the advanced biotechnological process. Interfacing biomolecules with the nanomaterials will result in the development of new tools and techniques that, in turn, will enable to explore the fundamental process at the nano level and fabricate cost-effective portable devices. Fascinating biomolecules like DNA, RNA and proteins in the regime of nanoscale are intelligent materials that are capable of storing the information and controlling the basic structure and function of the complex biological systems. Following this concept, the current pandemic situation would be a natural selection process, where the selective pressure is on the ssRNA of Covid-19 to choose the suitable progeny for survival. Consequently, the interaction of human DNA invoking response with Covid-19 happens at the nanoscale and it could be a better candidate to provoke combat against the virus. The extent of this interaction would give us the insights at the nanotechnological level to tackle the prevention, diagnosis and treatment for Covid-19. Herein, the possible features and obstacles in Covid-19 and a probable solution from the advent of nanotechnology are discussed to address the current necessity. Moreover, the perspective sustainable green graph mask that can be prepared using green plant extract/graphene (Bio-Nano composite mask) is suggested for the possible protection of virus-like Covid-19. The composite material will not only effectively trap the virus but also inactivate the virus due to the presence of antiviral compounds in the plant extracts